Acceptance of Rehabilitation Technology in Adults With Moderate to Severe Traumatic Brain Injury, Their Caregivers, and Healthcare Professionals: A Systematic Review. Issue 4 (July 2019) - Vaezipour, Atiyeh; Whelan, Brooke-Mai; Wall, Kylie; Theodoros, Deborah
Abstract : Background: Moderate to severe traumatic brain injuries (TBIs) commonly result in persistent physical, cognitive, and/or emotional deficits that require long-term rehabilitation. Technology-enabled rehabilitation provides an innovative alternative to traditional intervention models. End-user acceptance of these interventions, however, is a critical factor in determining the effective implementation and acceptance of these technologies. Objective: To systematically review the literature to identify methods and measures used to evaluate user acceptance relating to rehabilitation technologies for adults with moderate to severe TBI, their caregivers, and healthcare professionals. Methods: Six key databases including Medline, Embase, CINAHL, Cochrane, Scopus, and Web of Science were searched using the relevant search terms. Results: From a yield of 2059 studies, 13 studies met the eligibility criteria. The review revealed limited research that formally evaluated user acceptance in relation to rehabilitation technologies designed for adults with TBI. Furthermore, where such evaluations were conducted, comprehensive research designs incorporating theoretical frameworks of technology acceptance were sparse. Importantly, a range of technologies and recommendations that positively influenced user acceptance were identified. Future directions for research in this area include the use of theory-driven research designs to enhance our understanding of technology acceptance, to support the development of rehabilitation technologies that maximize functional outcomes for individuals with TBI.